PGPR Induced Differencial Expression of Defence Enzymes Regulating Resistance Against Colletotrichum Capsici in Turmeric - Adhipathi, P.; Nakkeeran, S.; Devi, P. Renuka; Velazhahan, R.; Raguchander, T. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Plant growth promoting Bacillus amyloliquefaciens strain BaTNAU5 and Pseudomonas fluorescens strain Pf3TNAU were evaluated in turmeric for induction defence by differential expression of defence enzymes against Colletotrichum capsici. Further the activity and quantitative assay of the defense enzymes peroxidase (POD), polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL), Î‘1,3-glucanase, chitinase, catalase and defense-inducing chemicals (total phenols) significantly increased with soil and foliar application of B. amyloliquefaciens (BaTNAU5) and P. fluorescens (Pf3TNAU). Western blot analysis of protein extracts from B. amyloliquefaciens (BaTNAU5) and P. fluorescens (Pf3TNAU) challenged with C. capsici, a chitinase with an apparent molecular weight of 28 kDa was induced four days after treatment.